If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-7(6x-7)+6=-42x+55
We move all terms to the left:
-7(6x-7)+6-(-42x+55)=0
We multiply parentheses
-42x-(-42x+55)+49+6=0
We get rid of parentheses
-42x+42x-55+49+6=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0
| -7(6x-7+6=-42x+55 | | -4(3y+1)-18=-9(y+4)+3y | | 4x+6=4(x-4) | | 4(3+v)+35v=10v | | x(x-4)=4(x-9) | | 0=12-0.03s^2 | | 3y+34=68 | | -0.5h(2h+3)=0 | | (2x+8)÷2-x=4 | | 15x+6x-19=3x | | x-16=40-2x | | 8x+16-6x+60=180 | | -34=7x-5-5x+5+2 | | 5(x-7)+4=-31 | | -+4-x+6x=4 | | −8+b/38=−9 | | −8+b38=−9 | | -2(2-2x)=4-8(1x) | | 0.01q^2+0.30q-105.91=0 | | 0=0.01q^2+0.30q-105.91 | | 5x-16=2x+23 | | 12x+19=5x+5 | | Y=-8+1.2x | | -5(x+1)-10=18+2 | | 7c=(108+165) | | 12/3x+6/1=4x+2 | | r/5.13=8 | | X-a+4=a | | 2(4z+14)=108 | | x+(6)=-3 | | (113-29)=14m | | (22+45)c=268 |